SNAI2 promotes the development of ovarian cancer through regulating ferroptosis. Issue 3 (1st March 2022) - Jin, Yunfeng; Chen, Li; Li, Li; Huang, Guoqin; Huang, Hua; Tang, Chunhui
ABSTRACT: This study aims to explore the regulatory mechanism of SNAI2 in ovarian cancer, and to uncover its correlation with ferroptosis. A human normal ovarian cell line IOSE-80 and four ovarian cancer cell lines (SKOV3, A2780 and CAOV3) were applied to detect SNAI2 and ferrptosis level, and an elevated SNAI2 expression and the occurrence of ferroptosis were observed in ovarian cancer cells, especially in SKOV3 cells. Then, results from a series of cellular behaviors experiments revealed that SNAI2 knockdown greatly suppressed cell viability, migration, invasion, and promoted cell apoptosis, as well as promoting the occurrence of ferroptosis in SKOV3 cells. The effects of SNAI2 knockdown on SKOV3 cells were similar to erastin, an inducer of ferroptosis. Subsequently, SNAI2 was verified to directly bind to the promoter of SLC7A11 by luciferase reporter assay and chromatin immunoprecipitation (ChIP) assay. Furthermore, mice were subcutaneously injected with SKOV3 cells to induce tumor formation. Erastin exhibited an anti-tumor effect on mice suffering from ovarian cancer, which was partly weakened by SNAI2 overexpression. In conclusion, this study disclosed that SNAI2 knockdown or erastin exhibited an anti-tumor activity in ovarian cancer by promoting ferroptosis, shedding new insights of the regulatory mechanism of SNAI2-mediated ferroptosis in ovarian cancer. Graphical abstract: uf0001